2023
DOI: 10.1128/spectrum.04252-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eleven RNA Extraction Methods for Poliovirus Direct Molecular Detection in Stool Samples

Abstract: Poliovirus, the causative agent of poliomyelitis, is a target of global eradication led by the World Health Organization since 1988. Direct molecular detection and genomic sequencing without virus propagation in cell culture is arguably a critical tool in the final stages of polio eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Chloroform-treated stool supernatant underwent RNA extraction using either QIAamp Viral RNA Mini Kits (#51106, used for samples processed August 2021 to September 2021) or Roche High Pure Viral RNA Kits (#11858882001, used for samples processed October 2021 to February 2022) according to manufacturers’ protocols using a volume of 140 µl and 200 µl of supernatant, respectively. RNA extraction kit selection was determined by kit availability, but both kits have been validated for the DDNS method 22 . Extracted RNA was stored at +4 °C during the preparation of the nested PCR if performed on the same day or −80 °C if delayed more than 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Chloroform-treated stool supernatant underwent RNA extraction using either QIAamp Viral RNA Mini Kits (#51106, used for samples processed August 2021 to September 2021) or Roche High Pure Viral RNA Kits (#11858882001, used for samples processed October 2021 to February 2022) according to manufacturers’ protocols using a volume of 140 µl and 200 µl of supernatant, respectively. RNA extraction kit selection was determined by kit availability, but both kits have been validated for the DDNS method 22 . Extracted RNA was stored at +4 °C during the preparation of the nested PCR if performed on the same day or −80 °C if delayed more than 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…IC invested substantial effort in the research, development, and implementation of direct detection with nanopore sequencing (DDNS) for poliovirus surveillance [ 59 , 60 , 61 , 62 ]. This included publications that characterized rapid and sensitive direct detection and identification of poliovirus from stool and environmental surveillance samples using nanopore sequencing [ 59 ] and an analysis of the time taken to detect and respond to polio outbreaks in Africa considering the potential impact of direct molecular detection and nanopore sequencing [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This included publications that characterized rapid and sensitive direct detection and identification of poliovirus from stool and environmental surveillance samples using nanopore sequencing [ 59 ] and an analysis of the time taken to detect and respond to polio outbreaks in Africa considering the potential impact of direct molecular detection and nanopore sequencing [ 60 ]. IC also published a comparison of eleven RNA extraction methods for direct molecular detection of polioviruses from stool [ 61 ] and a prospective validation study of DDNS that reported preliminary cost estimates [ 62 ]. IC also included poliovirus surveillance in a consortium effort that it led with the goal of defining a research agenda for broad environmental wastewater surveillance of pathogens [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optimized protocol for kit B was simpler and the reaction was faster than those of kit A; with the addition of all the primers at the start of reaction, the RT-PCR reaction finished within 2.5 h; however, the efficient amplification could negatively affect the detection rate of minor populations of PV strains in the mixtures ( Table 2 , see below discussion). Selection of commercially available kits is apparently a critical factor for the performance of the DD, including the extraction step of viral RNA [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%